Comparison of five allopatric fruit fly parasitoid populations (Psyttalia species) (Hymenoptera: Braconidae) from coffee fields using morphometric and molecular methods - Billah, M.K.; Kimani-Njogu, S.W.; Wharton, R. A.; Woolley, J.B.; Masiga, D. (Bulletin of Entomological Research 98 (1): 63-75, 2008)
Morphometric studies of five allopatric parasitoid populations (genus Psyttalia Walker) from coffee plantations in Cameroon (Nkolbisson), Ghana (Tafo) and Kenya (Rurima, Ruiru and Shimba Hills) and one non-coffee population (from Muhaka, Kenya) were compared with individuals of Psyttalia concolor (Szepligeti), a species released in several biological control programmes in the Mediterranean Region since the 20th Century. Analyses of wing vein measurements showed the second submarginal cell of the fore wing and its adjoining veins had the heaviest principal component weights and served as the main contributing variables in the diagnostic differentiation of the populations. Two populations (Rurima and Ruiru) were found to be the closest to each other and with the strongest phenetic affinity toward P. concolor (and forming one cluster). Populations from Shimba Hills (of unknown identity), Nkolbisson (P. perproximus (Silvestri)) and Tafo formed a second cluster and were separated from P. concolor. Comparison using amplified fragment length polymorphism (AFLP) also showed the Shimba, Nkolbisson and Tafo populations forming a cluster in a dendrogram generated from their genetic distances, with the Shimba and Tafo populations placed as the most closely related species. Based on consistent morphological similarities, morphometric and ecological data coupled with the genetic evidence from AFLP data, the Shimba population is suggested as belonging to the P. perproximus group and, thus, represents a new occurrence record in Kenya. Our results also support earlier conclusion from cross mating data that populations from Rurima and Ruiru belong to the Psyttalia concolor species-group.
Keywords: Morphometry; Allopatric populations; Parasitoids; Psyttalia; Phonetic affinity; Mahalanobis distance; AFLP; Genetic distance; Dendrogram; Species-group